Capacidad fitorremediadora de tarwi (Lupinus mutabilis Sweet) mediante incorporación de enmiendas orgánicas a suelos contaminados por mercurio procedente de actividad minera - Salas Sucaticona, Reynaldo (2025)
Soil contamination by heavy metals is one of the main environmental concerns facing the world today, it causes soil deterioration, produces toxic effects on the living ecosystem and public health, the present research aims to evaluate the phytoremediation capacity of tarwi (Lupinus mutabilis Sweet) by incorporating organic amendments to soils contaminated by mercury from mining activity. The research corresponds to the quantitative approach and experimental design, the percentage of total mercury removal was determined, foliar analysis of leaf, root and stem of tarwi, absolute growth rates (TAC) and relative (TRC) were calculated and the agronomic characteristics in the contaminated soil were evaluated. The results revealed that the best treatment was T4 (SC + EV + T) with a reduction of 2.079 mg/kg which is equivalent to a removal of 31.82 %. In relation to the absolute (TAC) and relative (TRC) growth rates were significantly different in all treatments (p < 0.05), where the maximum daily increase in length was 0.678 cm/day (TAC) and 4.149 %/day (TRC) corresponding to T4 (SC + EV + T), the addition of organic amendments increases the organic matter in the soil, being the T4 treatment (SC + EV + T) the best treatment with an increase of 249 %. In conclusion, the bioavailability of Hg in soils tends to decrease through the addition of organic amendments, the differences in growth rates are directly related to the organic matter content and the incorporation of organic amendments improved the agronomic characteristics of the soil.